Analisis Pengendalian Kualitas dan Usulan Perbaikan pada Proses Edging di PT Rackindo Setara Perkasa dengan Metode Six Sigma - Hendy Tannady; Calvin Chandra (Universitas Bunda Mulia, 2017)
This research aims to improve the quality of processes and products on PT Rackindo Setara Perkasa, especially in Meja A edging process. This research is using six sigma method with the steps of DMAIC (define, measure, analyze, improve, control). The results of this research is there are three types of defects that found in the edging process. The defects are existing on paper connection, paper edging is not long enough and the maal edging is stuck. Based on the Pareto diagram, the improvements focused on the problem of paper connection and paper edging that is not long enough. Both defects are analyzed using the fishbone diagram to describe the causes of defects. From the analysis that uses 5W1H and solution tree, the conclusion of this study are the identification of several factors that cause defects, and recommendations for improvement in edging process, by making a training for the operators of edging process, making the written SOP on edging machine, making instructions about the engine setting, additional facilities on the roller of edging machine and the addition of compressor unit. By doing the improvement, it is expected an increase of sigma value from 4,22 into 4,71.Keywords: Six Sigma, DMAIC, Statistical Tools, Capability Process, 5W1H